An analysis of job satisfaction towards oil palm plantation workers / Maazaitil Aisyah Bahruni - Bahruni, Maazaitil Aisyah (Faculty of Plantation and Agrotechnology, 2015)
In order to face this tight competition, firms must search for ways to improve the productivity and job satisfaction among their workforce to retain their human capital. There are many factors that correlate with workers turnover, but job satisfaction is mostly used as a main reason. To overcome this problem, organization is responsible to take a good care towards their human capital by constructing effective plan to meet their workers satisfaction. Therefore, the organization should think about the factors relating to workers' job satisfaction. Then, the objective of this study is to identify the relationship between work-related factors and worker's job satisfaction in oil palm plantation. Other than that, the aim is to discover which elements in work-related factors is most dominant on worker's job satisfaction in oil palm plantation. This study was conducted in four selected oil palm plantation organization in Johor. The research design was correlation and multiple regression analysis. As the result of this study found that most of workers were satisfied with the kind of work they do in their job (59.9%). Other than that, 66.9 percent of workers were satisfied with the work condition where they work that is provided by top management. Besides that, majority of workers were satisfied with their earning and they were equally paid based on their workload. The workers also satisfied with the overall quality of supervision they received in workplace. In addition, recognition program also give great impact toward overall workers' job satisfaction as well as co-workers factor. Based on the finding, all element in work-related factors (pay, working environment, work itself, supervision, co-workers, and recognition) studied in this paper has significant relationship on worker's job satisfaction in oil palm plantation. Meanwhile, the most influence factor contributed to worker's job satisfaction in oil palm plantation is pay factor. Thus, the results of this study provide a useful background for the development of strategies among employers to improve their labour workforce to achieve job satisfaction when working in oil palm plantation sector.